Total Harmonic Reduction in Distribution System Using Discrete Wavelet Transform - et. al., A.C.Mulla, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study of a discrete wavelet transform for an adaptive shunt compensator (STATCOM) to minimize THD in a large and small power utility system is presented in this paper. During loading conditions, THD analysis, such as harmonics in output currents, is also performed. This algorithm divides each line's non-sinusoidal output current into different frequency ranges in order to analyze different non-sinusoidal frequency parameters in order to find the ideal KW power component. The error of each sensed output current is used to find the ideal sinusoidal currents for the triggering of a voltage source inverter (VSI) that is acting as a STATCOM. The software validation results of the proposed control algorithm are addressed under various loading conditions. Under different loading conditions, the (THD) Total harmonic distortion in input current is less than 5%, which is appropriate according to IEEE519 and IEC requirements.